2019
DOI: 10.9734/jammr/2019/v29i230063
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Kinesio Taping in the Management of Knee Osteoarthritis

Abstract: Background: Knee osteoarthritis (OA) is one of the commonest chronic joint problems presenting with pain and stiffness. As a consequence, activities of daily living are limited and decline the quality of life. Kinesio tape (KT) has been popular in worldwide by its positive effects including reducing pain, relieving stiffness and improving function. However, the therapeutic application tension, direction and technique have not been identified yet and still weak evidence in OA knee. Aims: To find out the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…This improvement may be related to the pain relief effect of KT and regulation of muscle tone by KT. Besides, Nwe et al's 45 study also showed more significant reduction of pain, ROM, improving function and reduction in analgesics consumption was found in intervention group than control group in patients with OA knee. This inconsistent finding may also contribute from various severity levels of knee OA, although we failed to find the available evidence.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This improvement may be related to the pain relief effect of KT and regulation of muscle tone by KT. Besides, Nwe et al's 45 study also showed more significant reduction of pain, ROM, improving function and reduction in analgesics consumption was found in intervention group than control group in patients with OA knee. This inconsistent finding may also contribute from various severity levels of knee OA, although we failed to find the available evidence.…”
Section: Discussionmentioning
confidence: 90%
“…[33][34][35][36]39,40,42,43,45,47,48 However, only two studies (n=81) reported the KT group had no improvement of knee pain compared to that of the control groups. 38,44 A total of 13 studies (n=136) assessed knee pain intensity by using VAS 33,35,36,40,42,45,48 and four studies assessed pain intensity by using the Numeric Pain Rating Scale (NPRS). 34,39,41,47 Effectiveness of KT on Knee Joint ROM Out of the included trails, seven of them (n=422) had assed ROM.…”
Section: Effectiveness Of Kt On Pain Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it decreases the incidence of inflammation and oedema or swelling. Nwe, Tun, Aung, and Myaing (2019) demonstrated that when using Kinesio tape on knee joint with performing some traditional exercises in individuals with osteoarthritis, this led to positive results where it relieved pain, decreased stiffness of knee joint and led to improving the performance of knee joint compared to not using Kinesio tape . Doğan et al (2019) showed that when using Kinesio tape led to positive effect and improvement of flexion and extension of knee and increase in neuromuscular activity of knee.…”
Section: Introductionmentioning
confidence: 99%